Cycle and biological parameters of Clitostethus arcuatus (Coleoptera: Coccinellidae), whitefly predator, Siphoninus phillyreae, under laboratory conditions - Churata Salcedo, Julissa M. (2021)
The objective of this study is to determine biological cycle and parameters of Clitostethus arcuatus (Rossi), predator of Siphoninus phillyreae (Haliday). To obtain prey, olive seedlings were infested with S. phillyreae collected from olive groves in Tacna. In laboratory, the different stages of development of C. arcuatus recovered from the same olive groves, were confined in a breeding cage to obtain adults of the same age, which were matched in breeding units, and placed in a stove with circulating air at 24,2 ± 0,8 ° C and 36,0 ± 5,9% RH. They were observed daily until their death, and from their positions the development cycle was determined, which is 24 days, of which 3,80; 15,78 and 4,42 days were for the egg, larva and pupa stages, respectively. The biological cycle of C. arcuatus was 77,02 days. Oviposition capacity 136,35 eggs/female; egg viability of 71,43%; larval mortality 36,25%; predation capacity of LI 3,8 eggs/day, LII 5 eggs/day; LIII 8,2 and 3,6 eggs and nymphs/day respectively, LIV 11,4 and 3,4 eggs and nymphs/day respectively, adults 9,8; 4,6 and 1,4 eggs, nymphs and adults/day respectively; sex ratio 0,59 and longevity 53,02 days.